Paired pulse transcranial magnetic stimulation in the assessment of biceps voluntary activation in individuals with tetraplegia - Roumengous, Thibault; Thakkar, Bhushan; Peterson, Carrie L. (Frontiers in Human Neuroscience, 2022)
After spinal cord injury (SCI), motoneuron death occurs at and around the level of injury which induces changes in function and organization throughout the nervous system, including cortical changes. Muscle affected by SCI may consist of both innervated (accessible to voluntary drive) and denervated (inaccessible to voluntary drive) muscle fibers. Voluntary activation measured with transcranial magnetic stimulation (VATMS) can quantify voluntary cortical/subcortical drive to muscle but is limited by technical challenges including suboptimal stimulation of target muscle relative to its antagonist. The motor evoked potential (MEP) in the biceps compared to the triceps (i.e., MEP ratio) may be a key parameter in the measurement of biceps VATMS after SCI. We used paired pulse TMS, which can inhibit or facilitate MEPs, to determine whether the MEP ratio affects VATMS in individuals with tetraplegia. Ten individuals with tetraplegia following cervical SCI and ten nonimpaired individuals completed single pulse and paired pulse VATMS protocols. Paired pulse stimulation was delivered at 1.5, 10, and 30 ms inter-stimulus intervals (ISI). In both the SCI and nonimpaired groups, the main effect of the stimulation pulse (paired pulse compared to single pulse) on VATMS was not significant in the linear mixed-effects models. In both groups for the stimulation parameters we tested, the MEP ratio was not modulated across all effort levels and did not affect VATMS. Linearity of the voluntary moment and superimposed twitch moment relation was lower in SCI participants compared to nonimpaired. Poor linearity in the SCI group limits interpretation of VATMS. Future work is needed to address methodological issues that limit clinical application of VATMS.